Hubungan Antara Pengetahuan, Pendidikan Ibu, Pola Asuh dan Penyakit Infeksi dengan Kejadian Wasting pada Balita di Puskesmas Melolo - Irma Ivalda Kale; Marselinus Laga Nur; Anna Henny Talahatu; Lewi Jutomo (Yayasan Literasi Sains Indonesia, 2026)
Wasting is one of the forms of acute malnutrition in toddlers that can increase the risk of morbidity and mortality. Various factors such as maternal education, knowledge, parenting style, and infectious diseases contribute to the occurrence of wasting. This study aims to analyze the relationship between maternal education, knowledge, parenting style, and infectious diseases with the incidence of wasting in toddlers within the working area of Puskesmas Melolo. The research employs a quantitative approach with a case-control design. The sample consists of 72 toddlers, including 36 cases (wasting) and 36 controls (non-wasting). The case samples were determined using the Lemeshow formula and selected through simple random sampling based on nutritional status. Data were collected via interviews using questionnaires and then analyzed using bivariate analysis with Chi-square tests and odds ratio (OR) calculation at a 95% confidence interval. The results indicate that variables significantly associated with wasting are maternal knowledge (p=0.001; OR=5,200), feeding parenting style (p=0,001; OR=5,179), hygiene parenting style (p=0,000; OR=5,900), and infectious diseases (p=0,000; OR=6.000). Meanwhile, maternal education (p=0,326) and psychosocial parenting style (p=0,458) did not show significant associations. This study concludes that maternal behaviors, such as nutrition knowledge and proper parenting practices, have a stronger influence on a child's nutritional status than formal education. It is recommended that community and health workers enhance nutrition education and promote good parenting practices through Posyandu activities and health counseling to reduce the incidence of wasting in the Puskesmas Melolo area.